Saltwater Freshwater Art : contemporary Aboriginal art from the mid North Coast of NSW - Page, Alison; Ridgeway, Stephanie; Saltwater Freshwater Arts Alliance Aboriginal Corporation (Coffs Harbour, N.S.W. : Saltwater Freshwater Arts Alliance Aboriginal Corporation, 2011)
Annotation pending.
Keywords: Art, Aboriginal Australian -- New South Wales; Artists, Aboriginal Australian -- New South Wales -- 21st century; History - Biographies - Indigenous - Autobiographies; Art - Artists